Effectiveness of the standard WHO recommended retreatment regimen (Category II) for tuberculosis in Kampala, Uganda - Jones-López, Edward C.; Ayakaka, Irene; Levin, Jonathan; Reilly, Nancy; Mumbowa, Francis; Dryden-Peterson, Scott; Nyakoojo, Grace; Fennelly, Kevin; Temple, Beth; Nakubulwa, Susan; Joloba, Moses L.; Okwera, Alphonse; et al. (PLoS medicine, 2011)
Each year, 10%–20% of patients with tuberculosis (TB) in low- and middle-income countries present with previously treated TB and are empirically started on a World Health Organization (WHO)-recommended standardized retreatment regimen. The effectiveness of this retreatment regimen has not been systematically evaluated. Methods and Findings: From July 2003 to January 2007, we enrolled smear-positive, pulmonary TB patients into a prospective cohort to study treatment outcomes and mortality during and after treatment with the standardized retreatment regimen. Median time of follow-up was 21 months (interquartile range 12–33 months). A total of 29/148 (20%) HIV-uninfected and 37/140 (26%) HIV-infected patients had an unsuccessful treatment outcome. In a multiple logistic regression analysis to adjust for confounding, factors associated with an unsuccessful treatment outcome were poor adherence (adjusted odds ratio [aOR] associated with missing half or more of scheduled doses 2.39; 95% confidence interval (CI) 1.10–5.22), HIV infection (2.16; 1.01–4.61), age (aOR for 10-year increase 1.59; 1.13–2.25), and duration of TB symptoms (aOR for 1-month increase 1.12; 1.04–1.20). All patients with multidrug-resistant TB had an unsuccessful treatment outcome. HIV-infected individuals were more likely to die than HIV-uninfected individuals (p,0.0001). Multidrug-resistant TB at enrolment was the only common risk factor for death during follow-up for both HIV-infected (adjusted hazard ratio [aHR] 17.9; 6.0–53.4) and HIV-uninfected (14.7; 4.1–52.2) individuals. Other risk factors for death during follow-up among HIVinfected patients were CD4,50 cells/ml and no antiretroviral treatment (aHR 7.4, compared to patients with CD4$200; 3.0– 18.8) and Karnofsky score ,70 (2.1; 1.1–4.1); and among HIV-uninfected patients were poor adherence (missing half or more of doses) (3.5; 1.1–10.6) and duration of TB symptoms (aHR for a 1-month increase 1.9; 1.0–3.5). Conclusions: The recommended regimen for retreatment TB in Uganda yields an unacceptable proportion of unsuccessful outcomes. There is a need to evaluate new treatment strategies in these patients.
Keywords: WHO; Recommended Retreatment Regimen (Category II); Tuberculosis; Uganda